The role of central corticotrophin‐releasing factor receptor signalling in plasma glucose maintenance through ghrelin secretion in calorie‐restricted mice. (6th March 2021) - Kimura, Risa; Kondo, Daisuke; Takemi, Shota; Fujishiro, Miyuki; Tsukahara, Shinji; Sakai, Takafumi; Sakata, Ichiro
Abstract: Under severe calorie restriction (CR), the ghrelin‐growth hormone axis in mice is involved in the maintenance of plasma glucose levels. Ghrelin, a stomach‐derived acylated peptide, is up‐regulated by the sympathetic nerve in the negative energy status. Central corticotrophin‐releasing factor receptor (CRF‐R) signalling stimulates the sympathetic tone. The present study aimed to examine the effect of central CRF‐R signalling on the maintenance of plasma glucose concentrations in severe calorie‐restricted mice with the involvement of ghrelin. Intracerebroventricular injections of urocorin‐1 and urocorin‐2, which are natural ligands for CRF‐R1 and CRF‐R2, elevated plasma ghrelin concentrations and ghrelin elevation with an i.c.v. injection of urocorin‐1 was cancelled by atenolol (β1 adrenergic receptor antagonist) administration. We then established a mice model of 60% CR and found that the administration of [d ‐Lys3]‐GHRP‐6 (a ghrelin receptor antagonist) in mice under 60% CR reduced the plasma glucose concentration more compared to the vehicle mice. Similarly, the atenolol injection in mice under 60% CR significantly reduced the plasma glucose concentration, which was rescued by the co‐administration of ghrelin. An i.c.v. injection of the alpha helical CRH, a non‐selective corticotrophin‐releasing factor receptor antagonist, in mice under 60% CR significantly reduced the plasma glucose concentration, although the co‐administration of α‐helical CRH with ghrelin maintained plasma glucose levels. These results suggest that central CRF‐R signalling is involved in the maintenance of plasma glucose levels in mice under severe CR via the sympathetic‐ghrelin pathway. Abstract : Intracerebroventricular injections of urocorin‐1 and urocorin‐2 elevated plasma ghrelin concentrations. Central CRF‐R signalling stimulates the sympathetic nerve and releases norepinephrine from axon terminals to stimulate ghrelin secretion. Sympathetic nerve‐β1 adrenergic receptor‐ghrelin pathway is necessary and sufficient to prevent severe hypoglycaemia in CR mice.